انواع تفسير القرآن الكريم بالسنة النبویۃ: دراسۃ بحثیۃ: Kinds of the Qur’ānic exegeses by Prophetic Sunnah: A research Study (Al-Qamar, 2019)
Sunnah of Prophet Muhammad (Peace be upon him) is amongst the major sources of Qur’ānic exegesis. This article deals with the kinds of Qur’ānic exegesis by the Prophetic Sunnah. It classifies this interpretation into two main categories: first is the direct and clear elucidation of the Qur’ānic words and phrases, second is indirect tafsīr of the Qur’ānic verses and concepts. It discusses and explores various kinds of referred tafsīr.